Extremity compartment syndrome: A review with a focus on non-invasive methods of diagnosis - Novak, Martin; Penhaker, Marek; Raska, Pavel; Pleva, Leopold; Schmidt, Martin (Frontiers in Bioengineering and Biotechnology, 2022)
The article deals with an overview of acute extremity compartment syndrome with a focus on the option of noninvasive detection of the syndrome. Acute extremity compartment syndrome (ECS) is an urgent complication that occurs most often in fractures or high-energy injuries. There is still no reliable method for detecting ECS. The only objective measurement method used in clinical practice is an invasive measurement of intramuscular pressure (IMP). The purpose of this paper is to summarize the current state of research into noninvasive measurement methods that could allow simple and reliable continuous monitoring of patients at risk of developing ECS. Clinical trials are currently underway to verify the suitability of the most studied method, near-infrared spectroscopy (NIRS), which is a method for measuring the local oxygenation of muscle compartments. Less explored methods include the use of ultrasound, ultrasound elastography, bioimpedance measurements, and quantitative tissue hardness measurements. Finding a suitable method for continuous noninvasive monitoring of the syndrome would greatly improve the quality of care for patients at risk. ECS must be diagnosed quickly and accurately to prevent irreversible tissue damage that can occur within hours of syndrome onset and may even warrant amputation if neglected.